2020
DOI: 10.1002/admi.202000112
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Topographical Organization: Influence on Cicada Wing Wettability and Bactericidal Properties

Abstract: Numerous natural surfaces have micro/nanostructures that result in extraordinary functionality, such as superhydrophobicity, self‐cleaning, antifogging, and antimicrobial properties. One such example is the cicada wing, where differences in nanopillar geometry and composition among species can impact and influence the degree of exhibited properties. To understand the relationships between surface topography and chemical composition with multifunctionality, the wing properties of Neotibicen pruinosus (superhydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 56 publications
0
48
1
Order By: Relevance
“…In contrast to previously described highly ordered nipple arrays on insect eyes (41). Another study exploring the molecular organization of dragonfly wing epicuticle found that the major components identified were fatty acids and n-alkanes with even numbered carbon chains ranging from C 14 to C 30 (42).…”
Section: Discussioncontrasting
confidence: 62%
“…In contrast to previously described highly ordered nipple arrays on insect eyes (41). Another study exploring the molecular organization of dragonfly wing epicuticle found that the major components identified were fatty acids and n-alkanes with even numbered carbon chains ranging from C 14 to C 30 (42).…”
Section: Discussioncontrasting
confidence: 62%
“…The reduction in WCA, in comparison to their corresponding wing structures, demonstrates the change in topography as well as the change in surface chemistry. The outer epicuticle of cicada wings is mainly made up of fatty acids and long chain hydrocarbons that would contribute to the inherent hydrophobic nature of the wing nanostructures [ 20 ]. However, when the WCA of primary mold PEG surfaces was investigated, they were shown to be hydrophilic (WCA < 90°).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of surface chemistry, in addition to topographic effects, cannot be overlooked when discussing bacterial adhesion on structured materials. Roman-Kustas et al have completed some important work on looking at both the chemical composition of cicada wings, as well as how changes in surface chemistry affects bacterial cell adhesion [ 20 , 21 ]. Their work concluded that the surface chemical constituents on the wing play a role in the antimicrobial activity of the wings, in addition to the surface structures.…”
Section: Introductionmentioning
confidence: 99%
“…All hydrophobic surfaces (CA > 90°) can be enhanced to superhydrophobicity by the addition of a certain type of topography [ 20 , 24 , 25 ]. This may be the reason why superhydrophobicity of insect wing cuticle has been studied extensively from a morphological point of view [ 1 , 3 , 11 , 12 , 26 28 ]. However, often, superhydrophobicity is a result of a combination of surface topography, comprising features both on the micro- (greater than 1 µm) and nanoscale (less than 200 nm), and chemical heterogeneity at the micrometre scale [ 7 , 13 , 16 , 29 31 ].…”
Section: Introductionmentioning
confidence: 99%